17β-Estradiol inhibits vascular smooth muscle cell migration via up-regulation of striatin protein. (3rd August 2015) - Zheng, Shuhui; Chen, Xi; Hong, Shubin; Long, Lingli; Xu, Yuxia; Simoncini, Tommaso; Fu, Xiaodong
Abstract: Striatin, an estrogen receptor (ER)-interacting protein, plays an important role in estrogen's nongenomic actions in vascular endothelial cells. However, the role of striatin in VSMCs is unknown. Here, we investigated the role of striatin in estrogen-regulated VSMCs migration. 17β-Estradiol (E2) at 10 nM largely inhibited VSMCs migration, which was reversed by the silencing of striatin expression. E2 increased striatin protein expression in a dose- and time-dependent manner. ERα agonist PPT, but not ERβ agonist DPN, mimicked the regulatory effect of E2. The regulatory effect of E2 on striatin protein expression was blocked by the pure ER antagonist ICI 182, 780 or the mitogen-activated protein kinase inhibitor PD98059, but not by the phosphatidylinositol-3 kinase inhibitor wortmannin or Src inhibitor PP2, suggesting that E2 increased striatin protein expression via extracellular-signal regulated kinase 1/2 (ERK1/2). E2 resulted in phosphorylation of ERK1/2 in a time-dependent manner. The silencing of ERK1/2 largely abolished E2-enhanced striatin expression. Finally, the inhibitory effect of E2 on VSMC migration was reversed by ICI 182, 780 or PD98059. Taken together, our results indicate that E2 inhibits VSMC migration by increasing striatin expression via ERα to ERK1/2 pathway, which maybe helpful to understand estrogen's anti-atherogenic effect in VSMCs. Chinese abstract: Striatin，一种雌激素受体相互作用蛋白，在雌激素对血管内皮细胞的非基因作用中发挥非常重要的作用。然而，Striatin对血管平滑肌细胞的作用是未知的。在这里，我们研究Striatin在雌激素调节的血管平滑肌细胞迁移中的作用。17β- 雌二醇（E2）水平达到10 nM时很大程度上抑制VSMCs迁移，这是由于Striatin表达沉默的逆转。雌二醇增加striatin蛋白的表达是呈剂量和时间依赖的。ERα激动剂PPT，而不是ERβDPN，模仿雌激素的调节作用。E2对striatin蛋白表达的调节作用是通过纯雌激素受体拮抗剂ICI 182，780或丝裂原活化蛋白激酶抑制剂PD98059所阻断，而不是磷脂酰肌醇-3激酶抑制剂曼青霉素或酪氨酸激酶抑制剂，表明E2增加striatin蛋白表达是通过细胞外信号调节激酶1/2（ERK1 / 2）。E2使ERK1 / 2磷酸化是时间依赖性的。ERK1 / 2的沉默很大程度上抑制了E2 Striatin表达增强。最后，E2对血管平滑肌细胞迁移的抑制作用通过ICI 182780或PD98059所逆转。总之，我们的研究结果表明，E2通过ERα或激酶ERK1／2通路增强Striatin表达而抑制血管平滑肌迁移，这或许有助于理解雌激素作用于血管平滑肌细胞的抗动脉粥样硬化作用。